An acoustic and morphometric evaluation of the geographic distribution of Phyllomedusa burmeisteri (Anura: Phyllomedusidae), with comments on P-bahiana - Andrade, Felipe Silva de; Haga, Isabelle Aquemi; Carvalho, Thiago Ribeiro de [UNESP]; Martins, Lucas Borges; Giaretta, Ariovaldo Antonio (Univ Sao Paulo, Esalq, 2018)
A recent study, based on phylogenetic and phylogeographic multilocus approaches, detected two evolutionary units (BUR and BUR-RJ) within the range of P. burmeisteri. BUR has a wide distribution, whereas BUR-RJ is restricted to a small area coincident with the Serra do Mar mountain range in the Brazilian state of Rio de Janeiro. We evaluate if acoustic and morphometric data support these two major clades within P. burmeisteri that were proposed using molecular evidence. We also provide for the first time detailed morphometric data for adult males of P. burmeisteri (including topotypes) and the holotype of P. bahiana, and we revisit the comparative acoustic diagnosis between P. burmeisteri and P. bahiana. We were unable to distinguish BUR and BUR-RJ evolutionary units based on morphometric, acoustic or any other feature of external morphology or coloration. Given the high levels of similarity in morphometric and acoustic traits between P. burmeisteri and P. bahiana, these features appear not to be informative in the differentiation of the two sister species.
Keywords: amphibians; bioacoustics; Leaf Frogs; taxonomy